Impact of a Multifaceted Antimicrobial Stewardship Intervention in a Primary Health Care Area: A Quasi-Experimental Study - March-López, Pablo; Madridejos, Rosa; Tomas, Rosa; Boix, Lucía; Arcenillas, Paula; Gómez, Lucía; Padilla, Emma; Xercavins, Mariona; Martinez, Laura; Riera, Montserrat; Badia, Cristina; Nicolás, Jordi; et al. (Frontiers in Pharmacology, 2020)
The aim of the study was to evaluate the impact of a multifaceted antimicrobial stewardship intervention on antibiotic consumption in a primary health care (PHC) area in Spain. Quasi-experimental study conducted in a PHC area with nine PHC centers, a 400-bed acute care teaching hospital, and 18 nursing homes serving a population of 260,561. The intervention was based on the 2016 CDC Core Elements of Outpatient Antibiotic Stewardship publication and targeted 130 PHC physicians, 41 PHC pediatricians, 19 emergency physicians and 18 nursing home physicians. The components were commitment, actions for improving antibiotic prescribing, tracking and feedback, and education and experience. The primary outcome was overall antibiotic consumption. Secondary outcomes were consumption of antibiotics to treat pharyngotonsillitis, acute otitis media, acute sinusitis, acute bronchitis, and urinary tract infection (UTI), percentage of patients treated with specific antibiotics, and dispensing costs. Consumption was measured in defined daily doses per 1000 inhabitants per day (DID) and compared pre- and post-intervention (2016 vs. 2018). Overall antibiotic consumption decreased from 16.01 to 13.31 DID (-16.85%). Consumption of amoxicillin/clavulanic acid and quinolones decreased from 6.04 to 4.72 DID (-21.88%) and 1.64 to 1.23 DID (-25.06%), respectively. The percentage of patients treated with antibiotics decreased from 26.99% to 22.41%. The intervention resulted in cost savings of €72,673. Use of antibiotics to treat pharyngotonsillitis, UTI, and acute otitis media, sinusitis, and bronchitis decreased significantly. Our antimicrobial stewardship program led to a decrease in antibiotic consumption and significantly improved the use of antibiotics for the most prevalent PHC infections.